Student Engagement: The Effect of Flipped Classroom on Improving Critical Thinking Skills - Joni Indra Wandi; Nora Afnita; Azwar Ananda; Erianjoni Erianjoni; Syafri Anwar; Maria Montesori (Universitas Veteran Bangun Nusantara, 2023)
History subject is very urgent in social education and there are four skills that students must master in learning social education: analyzing skills, critical thinking skills, evaluating skills, and creating skills. This study aimed to analyze the effect of the flipped classroom method and learning engagement on students’ critical thinking skills in history lessons. This research used a quantitative approach with a quasi-experimental design. The used instruments in this research were observation sheets, questionnaires, and critical thinking tests. The data analysis used Two Way ANOVA. The results showed that the flipped classroom and student engagement affect the student's critical thinking skills. Historical teachers should apply this method by building a pleasant learning atmosphere so that student engagement and critical thinking skills of a student increase.